Self-drive network development for socio-economic tourism: a mixed-method approach - Nattakan Rattanapan; Suriyan Jomthanachai; Danuphon Tippong; Patcharaporn Bunlueng (Cogent Social Sciences)
This article describes a study that uses mixed-methods research to evaluate and develop the self-drive tourism network. For the data envelopment analysis (DEA) of the cross-efficiency model, routing evaluation indicators of road infrastructure and facilities, as well as sideway facilities, were selected as factors of traveling value. The survey technique with such a journey checklist and the stakeholder focus group approach from various related fields help to obtain valuable data. The evaluation results show that the optimization problem-solving tool of DEA is suitable for rating the valuableness of the route. Moreover, findings were shared by a wide range of stakeholders resulting in the completion of self-drive tourism networks represented by the different traveling plans to optimize socio-economic tourism. It is also possible to boost the tourism industry under the constraints of travel result from COVID-19 pandemic.